Принцип свободи в рішеннях Конституційного Суду України - Андриц, М. Р.; Andryts, M. R. (Одеса : Гельветика, 2020)
У статті проаналізовано втілення принципу свободи в процесі конституційного судочинства сучасної України. Виявлено різні аспекти розуміння Конституційним Судом України цього принципу, серед яких – аксіологічний, антропологічний, гносеологічний, онтологічний. Установлено, що аксіологічне розуміння принципу свободи випливає з природи свободи як фундаментальної цінності дієвої конституційної демократії. Виявлено, що антропологічне розуміння принципу свободи пов’язане з функціональним потенціалом свободи для розвитку особи та її соціалізації. З’ясовано, що гносеологічне розуміння принципу свободи обумовлюється методологічним потенціалом «свободи», а саме її здатністю: а) опосередковувати права людини та громадянина (наприклад, право на приватність, право на інформацію, право на працю, право на власність), б) визначати співвідношення інтересів особи, суспільства, держави, а відтак і поняття «публічний інтерес», «охоронюваний законом інтерес», «цензура», що дає змогу окреслювати межі прав людини. Обґрунтовано, що онтологічне розуміння принципу свободи формується внаслідок його зовнішнього закріплення у формі самостійного права на свободу, яке Конституційний Суд України визнає основоположним, невід’ємним, невідчужуваним конституційним правом людини, що охоплює можливості людини обирати свою поведінку, самостійно діяти, визначати пріоритети. Таке право пов’язано із загальнодозвільним принципом, згідно з яким особі дозволено робити все, що не заборонено законом. Сутнісна характеристика права людини на свободу як самостійного права полягає в забезпеченні життєдіяльності людини, вільної від зовнішнього втручання, за винятком обмежень, що встановлюються Конституцією та законами України. Доведено, що онтологічне розуміння принципу свободи проявляється також у процесі забезпечення так званих негативних прав – свобод особи, як-от: «свобода й особиста недоторканність», «свобода об’єднань», у тому числі й «свобода профспілок», «свобода мирних зібрань», «свобода пересування», «свобода вільного вибору місця проживання», «свобода світогляду». Аргументовано, що вказані свободи є формою втілення, «буття» досліджуваного принципу, а відтак їх перебування в полі зору конституційного контролю засвідчує реалізацію Конституційним Судом України ідеї свободи.

The article analyzes the application of the principle of freedom in the constitutional proceedings of Ukraine nowadays. Various aspects ofunderstanding by the Constitutional Court of Ukraine of this principle have been identified, including axiological, anthropological, gnoseological and ontological. It has been established that the axiological understanding of the principle of freedom arises out of thenature of freedom as a fundamental value of an effective constitutional democracy. It is revealed that the anthropological understanding of the principle of freedom is connected with functional potential of freedom for development of the personality and its socialization. It was found out that the gnoseological understanding of theprinciple of freedom is predetermined by the methodological potential of “freedom”, namely its ability: a) to mediate human and civil rights (for example, the right to privacy, the right to information, the right to work, the right to property), b) to determine the relationship between the interests of a person, society, and the state, and, consequently, the notion of “public interest”, “legally protected interest”, “censorship”, which makes it possible to outline the boundaries of human rights. It has been substantiated that the ontological understanding of the principle of freedom is formed as a result of its external consolidation in the form of an independent right to freedom, which the Constitutional Court of Ukraine recognizes as a fundamental, inalienable and imprescriptible human right, which covers the ability of the individual to choose his or her behavior, to act independently and to set priorities. This right is linked to the general permissive principle according to which a person is allowed to do everything that is not prohibited by law. The essential characteristic of the human right to freedom as an independent right lies in the provision of lifesustaining activity of the individual,free from external interference, with the exception of restrictions established by the Constitution and laws of Ukraine. It has been proved that the ontological understanding of the principle of freedom is also expressed in the process of ensuring so-called negative rights – the freedoms of a person, for example, “freedom and personal inviolability”, “freedom of association”, including “freedom of trade unions”, “freedom of peaceful assembly”, “freedom of movement”, “free choice of place of residence”, “freedom of world view”. It is argued that these freedoms are a form of embodiment, the “existence” of the principle under consideration, and, therefore, their being under constitutional control is evidenced by the implementation of the idea of freedom by the Constitutional Court of Ukraine.
Андриц М. Р. Принцип свободи в рішеннях Конституційного Суду України / М. Р. Андриц // Юридичний вісник. - Одеса : Гельветика - 2020. - № 1. - С. 320-328.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; rule of law; legal principles; human rights and freedoms; Соnstitutional court of Ukraine; principle of freedom; верховенство права; принципи права; права і свободи людини; Конституційний Суд України; принцип свободи